Evaluating tornado casualty rates in the United States. (August 2020) - Fricker, Tyler
Abstract: Tornadoes account for nearly one fifth of all natural hazard fatalities in the United States, yet there exist no general estimates of casualty rates across the country. Here tornado casualty rates are estimated for all casualty-producing tornadoes over the period 1995–2016 using tornado level information related to the population and total housing units within each damage path. The 22-year United States per-capita casualty rate is 2.3%, while the 22-year United States per-housing unit casualty rate is 5.4%. Injury and fatality rates are also estimated over the same period. The 22-year United States per-capita fatality rate is 0.15% and the per-capita injury rate is 2.1%. The per-housing unit fatality rate is 0.36% and the per-housing unit injury rate is 5.1%. Casualty rates are further examined through subsets of Enhanced Fujita rating, state boundaries, and county boundaries. When used in conjunction with estimates of future changes in tornado behavior and population growth, these casualty rates can help predict tornado casualty events in communities throughout the United States.